2014
DOI: 10.2337/db14-0153
|View full text |Cite
|
Sign up to set email alerts
|

GABA Promotes Human β-Cell Proliferation and Modulates Glucose Homeostasis

Abstract: γ-Aminobutyric acid (GABA) exerts protective and regenerative effects on mouse islet β-cells. However, in humans it is unknown whether it can increase β-cell mass and improve glucose homeostasis. To address this question, we transplanted a suboptimal mass of human islets into immunodeficient NOD-scid-γ mice with streptozotocin-induced diabetes. GABA treatment increased grafted β-cell proliferation, while decreasing apoptosis, leading to enhanced β-cell mass. This was associated with increased circulating human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
176
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(198 citation statements)
references
References 40 publications
15
176
0
Order By: Relevance
“…GABA considerably improved islet-cell survival in vitro. Moreover, it protected islet cells against apoptosis induced by cytokines [55], as well as rapamycin, tacrolimus, and mycophenolate mofetil [34]. As noted previously, these protective effects appear dependent on increased SIRT1 [38].…”
Section: Studies In Humansmentioning
confidence: 69%
See 1 more Smart Citation
“…GABA considerably improved islet-cell survival in vitro. Moreover, it protected islet cells against apoptosis induced by cytokines [55], as well as rapamycin, tacrolimus, and mycophenolate mofetil [34]. As noted previously, these protective effects appear dependent on increased SIRT1 [38].…”
Section: Studies In Humansmentioning
confidence: 69%
“…A major limitation of clinical islet transplantation is that the majority of islets die soon after transplantation due to a combination of factors; most notably hypoxia and an acute inflammatory response [52][53][54]. In studies with human cells, we demonstrated that GABA markedly reduced islet-cell apoptosis in culture, and stimulated insulin production [34,55]. Islet cells die spontaneously in culture, and commonly used immunosuppressive drugs further impair islet-cell survival [34,56].…”
Section: Studies In Humansmentioning
confidence: 94%
“…Numerous studies have shown that the phosphatidylinositol 3-kinase–Akt (PI3K/AKT) signaling pathway plays a major role in cell apoptosis (Tu et al, 2010; Shilpa et al, 2013; Purwana et al, 2014; Di et al, 2015; Liu et al, 2015). The specific involvement of the GABA B receptor in Akt activation has been investigated in several types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin secretion is controlled by a variety of neurotransmitters and hormones [1][2][3]. The insulin-secreting pancreatic β cells share many features with other neuroendocrine cells.…”
Section: Introductionmentioning
confidence: 99%